2018
DOI: 10.1071/sr17278
|View full text |Cite
|
Sign up to set email alerts
|

Why copper and zinc are ineffective in reducing soil urease activity in New Zealand dairy-grazed pasture soils

Abstract: Micronutrients copper (Cu) and zinc (Zn) have the potential to inhibit soil urease activity (UA) and reduce ammonia (NH3) emissions over long duration (8–12 weeks) but have not been tested for reducing NH3 losses from cattle urine deposited in dairy-grazed pasture soils. The objective of this study was to assess the effectiveness and longevity of Cu and Zn in reducing soil UA, for the use of these metals to reduce NH3 emissions from deposited urine by grazing cattle. A series of experiments were conducted to (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In contrast, CuSO 4 addition at 5 mg kg –1 induced negligible effects on the activity of urease at 10 h (Figure a), even though the concentrations of bioavailable Cu in soil treated with CuSO 4 were higher than those with Cu­(OH) 2 nanopesticide or nano-Cu­(OH) 2 . Negligible changes in the activity of urease were also observed by Adhikari et al, who investigated effects of copper and zinc on urease activity in New Zealand dairy-grazed pasture soils. Here, measurable changes in the activity of urease were observed in soil treated with 50 mg kg –1 of CuSO 4 after 10 h of incubation (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, CuSO 4 addition at 5 mg kg –1 induced negligible effects on the activity of urease at 10 h (Figure a), even though the concentrations of bioavailable Cu in soil treated with CuSO 4 were higher than those with Cu­(OH) 2 nanopesticide or nano-Cu­(OH) 2 . Negligible changes in the activity of urease were also observed by Adhikari et al, who investigated effects of copper and zinc on urease activity in New Zealand dairy-grazed pasture soils. Here, measurable changes in the activity of urease were observed in soil treated with 50 mg kg –1 of CuSO 4 after 10 h of incubation (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Metal-based manufactured nanomaterials, such as ZnO-NPs, CuO-NPs, and Ag-NPs, would likely release metal ions under aerobic conditions, which may impose impacts on soil bacteria, with changes in the activity of enzymes, such as acid phosphatase, , which is also highly dependent upon soil properties, such as organic matter content. For example, a recent study reported that additions of Cu to organic carbon-rich pasture soil achieved negligible reductions in urea hydrolysis as a result of the interaction of bioavailable Cu with labile soil organic carbon and clay particles . Nevertheless, no data were available to illustrate the impacts of a commercial Cu­(OH) 2 NPF on the soil enzyme activity and bacterial community, especially compared to its conventional ionic analogue CuSO 4 , restricting a comprehensive environmental risk assessment of the Cu­(OH) 2 nanopesticide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urease is the enzyme that catalyzes the hydrolysis of urea to carbon dioxide and ammonia. A large increase in the activity of this enzyme in a short period of time results in the loss of urea fertilizers due to its volatilization as ammonia, causing environmental pollution problems [34]. Since the highest increment was found for the SHFX treatment (Figure 1), the organic matter included in the TX product affected the microbiota in soils with good aeration.…”
Section: Discussionmentioning
confidence: 99%
“…They include iron, zinc, copper, boron, manganese, molybdenum, and chlorine. The micronutrient content of soils depends upon the soil types, parent material, soil pH, organic matter, clay content, amount of exchangeable bases, and phosphate [2,3].…”
Section: Introductionmentioning
confidence: 99%